2011
DOI: 10.1111/j.1439-0426.2011.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating sturgeon conservation and rehabilitation measures in Turkey: an overview on major projects (2006-2009)

Abstract: Summary The aim of this report is to provide an overview of the current status of efforts on the potential rehabilitation of sturgeon populations in Turkish waters, describing the structure and the outcome of projects carried out since 2006 and identifying the strategic needs for sturgeon conservation measures at a national level. It is well known that there were six sturgeon species occurring around Turkish Black Sea coasts while entering the rivers, mainly Kızılırmak, Yeşilırmak, Sakarya and Çoruh Rivers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…However, population recovery and favourable conservation status cannot be achieved and sustained under the ongoing threats of habitat degradation and loss and intensified illegal sturgeon trading in the region (Akbulut et al, 2011;Jahrl et al, 2021).…”
Section: Demographic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, population recovery and favourable conservation status cannot be achieved and sustained under the ongoing threats of habitat degradation and loss and intensified illegal sturgeon trading in the region (Akbulut et al, 2011;Jahrl et al, 2021).…”
Section: Demographic Analysesmentioning
confidence: 99%
“…This is not the case in the southern Black Sea region where there has been no restocking and the only recovery measure has been the implementation of a fishing Sporadic spawning events are known for the Danube River, downstream of the Iron Gates Dams Honț et al, 2018), where the presence of young-of-the-year stellate sturgeon has been monitored since 2000 Paraschiv et al, 2017). In contrast, spawning migration has rarely been observed or has ceased for most of the sturgeon species of the Turkish rivers (Akbulut et al, 2011). The conditions needed for Given the scarcity of the stellate sturgeon individuals available for the study and the slight signs of the population recovery in the NW-BS region, it is vital to increase the efforts to enforce and prolong the fishing ban by all Black Sea countries.…”
Section: Key Information For the Management Of Population Recovery An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sturgeon species composition in Turkey was reviewed several times (see Akbulut et al [2011] for details) and the results showed that there are seven species belonging to the Family Acipenseridae (Huso huso, Acipenser sturio, Acipenser stellatus, Acipenser gueldenstaedtii, Acipenser nudiventris, Acipenser ruthenus, Acipenser persicus). These species are distributed in the Turkish Black Sea coastal waters, with some of them entering the freshwater system [Bat et al 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive fishing and habitat degradation have impacted many sturgeon populations worldwide (Bemis and Kynard, ; Pikitch et al., ; Bloesch et al., ; Rosenthal et al., , ). Following a dramatic decline in the wild sturgeon population, hatchery‐reared fish are often released to enhance or restore threatened or extinct sturgeon populations for conservation and recreational fishing (Akbulut et al., ; Shuman et al., ). However, there are many differences between the hatchery environment and the wild (e.g.…”
Section: Introductionmentioning
confidence: 99%